Diabetic cardiomyopathy: Clinical phenotype and practice - Zhao, Xudong; Liu, Shengwang; Wang, Xiao; Chen, Yibing; Pang, Pai; Yang, Qianjing; Lin, Jingyi; Deng, Shuaishuai; Wu, Shentao; Fan, Guanwei; Wang, Bin (Frontiers in Endocrinology, 2022)
Diabetic cardiomyopathy (DCM) is a pathophysiological condition of cardiac structure and function changes in diabetic patients without coronary artery disease, hypertension, and other types of heart diseases. DCM is not uncommon in people with diabetes, which increases the risk of heart failure. However, the treatment is scarce, and the prognosis is poor. Since 1972, one clinical study after another on DCM has been conducted. However, the complex phenotype of DCM still has not been fully revealed. This dilemma hinders the pace of understanding the essence of DCM and makes it difficult to carry out penetrating clinical or basic research. This review summarizes the literature on DCM over the last 40 years and discusses the overall perspective of DCM, phase of progression, potential clinical indicators, diagnostic and screening criteria, and related randomized controlled trials to understand DCM better.